Menstrual psychosis. (10th March 2022) - Ahern, E.; Cohen, D.; Prior, C.; Raji, E.
Abstract : In this report, we explore a case of symptoms consistent with menstrual psychosis. In order to do this, a review of the literature relating to this topic was conducted and a report was written. This is a case of a previously well adolescent female who experienced psychotic symptoms in the pre-menstrual phase of her cycle and became well soon after her menstrual period began. These episodes were prevented by aripiprazole, but recurred once medication was withdrawn. We conclude that psychosis in some women may have a relationship with the menstrual cycle. In women presenting with psychosis, it may be appropriate to note menstrual variation in symptoms. This could have a potential role in individualisation of treatment for women with psychotic disorders.